Maslahah, Gender, dan Konstitusi dalam Diskursus Batas Kedewasaan Menikah Pasca-Putusan MK No. 22/PUU-XV/2017 - Machrus Ali Syifa’ (CV. Kalimasada Group, 2026)
Changes in the minimum age limit for marriage have become an important issue in family law in Indonesia, especially following the Constitutional Court Decision Number 22/PUU-XV/2017 which emphasizes the aspects of equality and protection of children's rights. This article evaluates the legal reasoning behind the Constitutional Court (MK) Decision Number 22/PUU-XV/2017 concerning the minimum age of marriage for women. The study employs two primary analytical frameworks: the concept of maslaẖah proposed by Muẖammad Saʻîd Ramaḏân al-Bûṯî and the Islamic paradigm of gender equality. This study aims to analyze the legal rationality of the Constitutional Court Decision Number 22/PUU-XV/2017 regarding the age limit for marriage from the perspective of maslaẖah and Islamic gender equality. The findings of this research confirm three main points. First, the constitutional judges' ratio decidendi for revising the age limit is grounded in the arguments of eliminating discrimination, ensuring health and educational rights, preventing child exploitation, comparative legal reviews across various countries, and the urgency for policy reform. Second, from the perspective of al-Bûṯî's maslaẖah, standardizing the marriageable age for both men and women does not constitute a public interest (maslaẖah), given the failure to fulfill the five fundamental parameters of maslaẖah that he established. Third, viewed through the lens of Islamic gender equality, the decision is deemed incongruent. This is based on the principle that equivalence in Islam does not imply absolute uniformity or strict equalization; rather, it emphasizes proportional justice focused on the fulfillment of rights corresponding to their specific needs.